Environmental and biological tin and lead chemistry - Healy, Michael Anthony (1980)
Tin and lead are metals of considerable commercial importance and are used in many forms in the environment. Heat and light stabilization of polyvinylchloride polymer by organotins is now a principle application of that metal. The spectroscopic properties and crystal structures are determined for some estertin precursors of these stabilizers: mono and bis-(beta-carbomethoxyethyl) tin chlorides, as well as the bis-(beta-carbomethoxyethyl) tin dichloride analogue. The feasibility of using Mössbauer spectroscopy to determine the fate of the organotin species within the PVC is also assessed. The INDOR technique is used to obtain tin-119 n. m. r. data for a series of trimethyl and dimethyltin(IV) compounds and the results interpreted in a manner illustrating the use of this method as a structural probe for the solution chemistry of organotin systems. In the case of lead, attention is given to the effects of use of that metal in petrol by examining its overall distribution pattern in the dust, soil, grasses, plants and fruit of a roadside environment. Additionally a new aetiology of lead poisoning involving some traditional Asian medicines and cosmetics is also described and a route for gastrointestinal absorption of lead sulphide from this source proposed. The effect of particle size on uptake rate is established. A chemical model for interaction between body-phosphate systems and lead derived from such sources as those studied is designed. The reactions found to occur between lead acetate, lead nitrate and dimethylphosphite and trimethylphosphate are interpreted. Preliminary studies show reaction between lead and adenosine di- and triphosphate and the data obtained from the model systems are used to elucidate the reaction pathway with these body-phosphate systems.